Hubungan Dukungan Keluarga dengan Kepatuhan Diet pada Pasien Diabetes Melitus Tipe 2 - Susi Susanti; Nurambiya; Samsudin La Ami (Journal of Legal and Cultural Analytics, 2022)
Relationship between family support and diet compliance in type 2 diabetes mellitus patients at. The importance of family support to participate in maintaining the recommended food or diet for family members who suffer from diabetes mellitus. One form of patient compliance is by following the dietary recommendations suggested by nutritionists..To determine the relationship between family support and dietary compliance in Type 2 Diabetes Mellitus Patients at. The type of research used is quantitative with a descriptive research design using a cross sectional approach. To determine the relationship between the independent variable and the dependent variable by using a joint measurement, the total population is 30 people, the sampling of this study used a random sampling technique so that the results were 30 respondents, the data measurement instrument used a questionnaire. there is a relationship between family support and adherence to a type 2 diabetes mellitus. The p-Value = 0.004 (α<0.05). There is a relationship between family support and adherence to a type 2 diabetes mellitus diet at.